CALCULATION OF BASIC THERMODYNAMIC CHARACTERISTICS OF THE SYSTEMS C-H-O, AR, AND N2 UNDER THE PT-CONDITIONS OF THE EARTH'S CRUST AND UPPER MANTLE - Vorontsova O.V.; Zubkov V.S. (My University, 2000)
A computing scheme for estimating the isothermal increments of main thermodynamic characteristics of gases under the geobarometrical conditions of the Earth's crust and upper mantle has been developed. An FGL unit built into the program complex Selektor-C has been elaborated from this computing scheme. When isothermal changes in thermodynamic parameters of gases in the range from 1 to P bar cannot be determined by one equation of state, advantage is taken of a step-like method for calculating the isothermal increments using a priority set of several equations.